Latin America's Emerging Middle Classes
XXV, 209 p.
Keywords: Politicians, business leaders and citizens look with hope to the Latin American middle class for political stability and purchasing power, but the economic position of the middle class remains vulnerable. The contributors document the remarkable emergence of this middle group in Latin America, whose measurement turns out not to be an easy task.